Evidence of Stage Shift in Women Diagnosed With Ovarian Cancer During Phase II of the United Kingdom Familial Ovarian Cancer Screening Study. Issue 6 (June 2017) - Rosenthal, Adam N.; Fraser, Lindsay S. M.; Philpott, Susan; Manchanda, Ranjit; Burnell, Matthew; Badman, Philip; Hadwin, Richard; Rizzuto, Ivana; Benjamin, Elizabeth; Singh, Naveena; Evans, D. Gareth; Eccles, Diana M.; et al.
Abstract : (Abstracted from J Clin Oncol 2017:35(13):1411–1420) For the randomized general population, the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) investigated a new multimodal screening test using the Risk of Ovarian Cancer Algorithm (ROCA), which interprets serial CA-125 results, and transvaginal sonography as a second-line test. High sensitivity and specificity were achieved with this test.